2021
DOI: 10.1037/dhe0000190
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-reality simulations to build capacity for advocating for diversity, equity, and inclusion in the geosciences.

Abstract: We report on data collected at 3 time points during a 1-year intervention designed to teach a purposive sample of geoscience faculty members (n ϭ 29) from 27 universities throughout the United States how to identify and address issues related to diversity, equity, and inclusion in their departments. For the intervention we used mixed-reality simulations to help participants practice specific skills to address common situations in geoscience departments. The intervention also included an intensive 3-day worksho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…After the intervention program was implemented, people's self-and collective competencies to recognize equality, diversity, and social inclusion increased significantly. In the measurements after 1 year, it was observed that self-efficacy was considerably higher than the pre-test measurements (Chen et al, 2020 ). To sum up, this intervention study that has been carried out recently with an adult sample has also effective and important results that emphasize ethnic diversity and equality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the intervention program was implemented, people's self-and collective competencies to recognize equality, diversity, and social inclusion increased significantly. In the measurements after 1 year, it was observed that self-efficacy was considerably higher than the pre-test measurements (Chen et al, 2020 ). To sum up, this intervention study that has been carried out recently with an adult sample has also effective and important results that emphasize ethnic diversity and equality.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting intervention program aimed to increase advocacy for diversity, equality, and social inclusion was also conducted with the participation of faculty members from different universities in the United States (Chen et al, 2020 ). The content of the intervention program which was carried out with 29 faculty members consisted of recognizing and defining ethnic differences, equality, and social inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Within the geosciences (Earth, Atmosphere, Ocean, and Polar Sciences), there is a current wave of energy and attention to issues of equity and social justice in geoscience spaces that is long overdue. Calls to action (Ali et al., 2020; Morris et al., 2020), publications (e.g., Chen et al., 2020; Marín‐Spiotta et al., 2020), personal stories (#BlackAndStem (#BlackAndStem was created by Stephanie Page, PhD; twitter: @ThePurplePage)), new centers (e.g., AGU Ethics and Equity Center), and emerging movements (URGE: https://urgeoscience.org/) are pushing the edges and reforming approaches to broadening participation. This is encouraging, as past strategies to accelerate demographic and ethnocultural representation have not succeeded as hoped.…”
Section: Introductionmentioning
confidence: 99%
“…
Despite growing demographic diversity in the United States population at large, in the 50 years that the National Science Foundation has been keeping demographic statistics, there has been a continuing lack of diversification in the Science, Technology, Engineering and Mathematics (STEM) workforce, leading to growing frustration and a compelling need for both equity and inclusion (Bernard & Cooperdock, 2018).Within the geosciences (Earth, Atmosphere, Ocean, and Polar Sciences), there is a current wave of energy and attention to issues of equity and social justice in geoscience spaces that is long overdue. Calls to action (Ali et al, 2020;Morris et al, 2020), publications (e.g., Chen et al, 2020;Marín-Spiotta et al, 2020), personal stories (#BlackAndStem (#BlackAndStem was created by Stephanie Page, PhD; twitter: @ThePurplePage)), new centers (e.g., AGU Ethics and Equity Center), and emerging movements (URGE: https://urgeoscience. org/) are pushing the edges and reforming approaches to broadening participation.
…”
mentioning
confidence: 99%
“…Students of color and other marginalized students (e.g., those from lower and working social classes) have characterized their experiences in graduate school by the lack of meaningful and reciprocally trusting mentorship, belongingness and social integration, and mental health supports (Brunsma et al, 2017;Fosnacht & Calderone, 2020;Truong et al, 2016). These reports are explained in part by the large disparities in cultural representation among faculty and students, by a lack of awareness from professionals regarding issues students face surrounding DEI, and by a lack of institutional mechanisms that explicitly support students from culturally underserved backgrounds (Chen et al, 2020;Harris & Lee, 2018).…”
mentioning
confidence: 99%